Variations in radon concentrations in the underground waters during the generation and occurrence of seismic events in the Baikal region - A. K. Seminsky (Геодинамика и тектонофизика)
The purpose of this work is to analyze the variations of radon volumetric activity in groundwater from the South Angara region and to identify and study the response of the emanation field to the most significant seismic events that occurred in the Baikal region in 2021. To achieve this goal, we organized daily monitoring of the radioactivity of groundwater in the study area. The analysis of the obtained series made it possible to determine the amplitude of fluctuations of radon volumetric activity Q (from 13.2 to 48.4 Bq/L), as well as the average annual (26 Bq/L) and daily average (4.5 Bq/L) indicators.The total number of earthquakes that occurred during the year on the territory of the Baikal region yielded a sample of 40 most significant (M≥4) events, for which the radii of the areas of influence were calculated. In three cases, we found that the sampling points were located within the influence radii or close to it. In four cases, the actual distances from the monitoring points to the epicentres were one and a half to three times greater than the calculated radii, and in the rest thirty-three cases, these distances were more than three times greater than that.Three types of emanation responses to seismic events have been identified, with one of which to be recorded before an earthquake, that is, to be a prognostic sign. Among the earthquakes demonstrating this effect, the Khubsugul earthquake was the strongest in the study area over the past ten years. Grouping by distance from the source to the sampling point relative to the radius of the event’s influence practically coincides with the set of earthquakes by the recording time and the type of recorded responses.Thus, the fluctuations of the emanation field spread over considerable distances from the earthquake generation area with gradual attenuation, and the response recording moment and the type of anomaly that appeared on the graph depend on the power of an impending event, as well as on the distance between the earthquake epicentre and the sampling point. The study shows that the possibility of identifying the emanation precursor effects before strong earthquakes on the territory of the Baikal region is based on two primary conditions: first, sufficient strength of an impending earthquake; second, the location of the sampling point within the radius of the area of influence of this earthquake.